Green Light Partial Replacement of Red and Blue Light Improved Drought Tolerance by Regulating Water Use Efficiency in Cucumber Seedlings - Ma, Yuting; Hu, Linli; Wu, Yue; Tang, Zhongqi; Xiao, Xuemei; Lyu, Jian; Xie, Jianming; Yu, Jihua (Frontiers in Plant Science, 2022)
Green light has been proved to enhance plant defense against biotic and/or abiotic stress. To illustrate the effects of green light partially replaced red and blue light on plant under drought condition, cucumber seedlings were treated with short-term drought stress and were concomitantly exposed to four treatments, which were set up by adjusting the relative amount of green light as 0 (RB), 25 (RBG25), 50 (RBG50), and 75 (RBG75) µmol m−2 s−1, respectively, with a total photosynthetic photon flux density of 250µmol m−2 s−1 and a fixed red-to-blue ratio of 4:1. The results showed that: compared with RB, RBG50 significantly increased shoot fresh and dry weight, root dry weight, plant height, stem diameter, leaf area and LMA by 10.61%, 7.69%, 66.13%, 6.22%, 10.02%, 4.10% and 12.41%, respectively. Also the addition of green light significantly increased the root volume and root tips number. Moreover, green light partial replacement of red and blue light increased total water content, especially free water content, and improved leaf water status, alleviated water loss in plants caused by drought stress. Also the addition of green light increased Pn, reduced both gs and Tr, enhanced the WUE and iWUE of leaves, and increased chlorophyll a and b content. Green light substituting proportion of blue and red light regulated stomatal aperture by significantly increasing ABA and GABA content. And the increase of GABA was result from the up-regulation of CsGAD2. However, the relative electrolytic leakage and contents of MDA, O2-and H2O2 vigorously decreased as the intensity of green light was added to the spectrum under drought. Conclusively, green light partially replaced red and blue light improved drought resistance of cucumber seedlings through up-regulated the expression of CsGAD2 gene and promote the synthesis of GABA. The increase of GABA content further down-regulated the expression of CsALMT9 gene, induced stomata closed, improved water utilization and alleviating damage caused by drought. This study highlights a role for green light in plant physiological processes. Moreover, analyzing the function of green light on improving drought resistance of plants could open alternative avenues for improving plant stress resilience.